1997
DOI: 10.1016/s0014-5793(96)01396-8
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of dimer formation of the cytoplasmic domain of a transmembrane osmosensor protein, EnvZ, of Escherichia coli using Ni‐histidine tag affinity chromatography

Abstract: EnvZ is a transmembrane osmosensor which regulates the phosphorylation of OmpR, a transcription factor for ompF and ompC genes which encode the major outer membrane porin proteins, OmpF and OmpC in Escherichia coli. Autophosphorylation of EnvZ occurs through a transphosphorylation reaction between two EnvZ molecules. To elucidate the molecular mechanism of signal transduction by EnvZ, we examined the dimer formation of the EnvZ cytoplasmic domain [EnvZ(C)]. For this purpose, we developed a method to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…2a. Because it has been demonstrated that EnvZ(C) forms a dimer (20,26), the present result indicates that the region required for the dimer formation resides in the 67 residue of subdomain A. This domain also contains the region required for OmpR interaction, because OmpR was trapped on the resin only in the presence of His-tagged subdomain A (compare lane 4 and lane 5 in Fig.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…2a. Because it has been demonstrated that EnvZ(C) forms a dimer (20,26), the present result indicates that the region required for the dimer formation resides in the 67 residue of subdomain A. This domain also contains the region required for OmpR interaction, because OmpR was trapped on the resin only in the presence of His-tagged subdomain A (compare lane 4 and lane 5 in Fig.…”
Section: Resultssupporting
confidence: 53%
“…After the sample was washed three times with buffer II [50 mM sodium phosphate buffer (pH 6.0)͞0.3 M NaCl͞5% glycerol] by using ultrafree-MC centrifugal filters (Millipore), proteins bound to Ni-NTA resin were eluted with 0.2 M imidazole/buffer II. The binding experiments between OmpR and either H6-EnvZ(C)⅐wt or H6-EnvZ(C)⅐(223-289) were carried out as described (26). The proteins eluted with 0.2 M imidazole/ buffer II in each binding assay were subjected to SDS͞PAGE (20% gel) and then stained with silver (27).…”
Section: ј-Tatgcaccatcaccatcacca-3јmentioning
confidence: 99%
“…Most mutations that cluster near or at the site of phosphorylation result in a locked high osmolarity phenotype. Mutations and deletions of the linker region exhibit various low and high osmolarity locked phenotypes and provide evidence that this region is critical for signalling (Park & Inouye 1997). Periplasmic deletions result in a locked high osmolarity phenotype or have no effect (reviewed in Forst & Roberts 1994;Leonardo & Forst 1996).…”
Section: Genetic Analysismentioning
confidence: 99%
“…In contrast, two EnvZ phosphatase mutants cannot complement each other which implies that the kinase and phosphatase activities may be regulated as a dimer to monomer transition, respectively. The K a for EnvZ dimerization has been estimated at 10 5 M ¹1 (Hidaka et al 1997).…”
Section: Catalytic Domainmentioning
confidence: 99%
“…WalK cytoplasmic domains have been purified, and results of in vitro studies show that they are autophosphorylated and phosphorylate their cognate RRs (6,7,17,31,32). Cytoplasmic or truncated forms of HKs have been reported to dimerize in vitro (15). In addition, a solution-state nuclear magnetic resonance (NMR) study (30) described dimerization of the homodimeric core domain of EnvZ, which belongs to the same Pho subfamily of HKs as WalK.…”
mentioning
confidence: 99%